City Limits: Boundary Conditions and the Building-Cities of Science Fiction. Issue 2 (3rd August 2018) - Butt, Amy
Can the rigidly bound city-buildings of science fiction (SF) provide a critical space to resist a movement towards structural divisions within the urban realm? Drawing on the growing body of urban studies research that utilizes the radical imagination and cognitive estrangement of SF as tools for critiquing the modern city, this paper focuses on three SF texts which explicitly address the architectural and social implications of extreme urban enclosure: Larry Niven and Jerry Pournelle's Oath of Fealty (1981 ), Isaac Asimov's Caves of Steel (1953) and James Blish and Norman Knight's A Torrent of Faces (1967). In each, the implications of gated communities are extrapolated and exaggerated to offer a glimpse into societies where a physical boundary creates spatial privilege by intensifying difference. By providing an estranging and critically distanced perspective on urban enclosure, these novels support existing movements to identify and resist damaging social division and structural segregation in the cities we currently inhabit.